Molecular phylogeny of Neotropical monogeneans (Platyhelminthes: Monogenea) from catfishes (Siluriformes) - Mendoza-Palmero, Carlos A; Blasco-Costa, Isabel; Scholz, Tomáš (Parasites & vectors, 2015)
BACKGROUND: The phylogenetic relationships of dactylogyrids (Monogenea: Dactylogyridae) parasitising catfishes (Siluriformes) from the Neotropical region were investigated for the first time. METHODS: Partial sequences of the 28S rRNA gene of 40 specimens representing 25 dactylogyrid species were analysed together with sequences from GenBank using Bayesian inference, Maximum likelihood and Parsimony methods. Monophyly of dactylogyrids infecting catfishes and the Ancyrocephalinae was evaluated using the Approximately Unbiased test. RESULTS: The Ancyrocephalinae is a paraphyletic group of species clustering in three main clades as follows: (i) clade A comprising freshwater dactylogyrids from the Holarctic parasitising perciforms clustering together with species (Ameloblastella, Unibarra and Vancleaveus) parasitising Neotropical catfishes; (ii) clade B including species of Dactylogyrus (Dactylogyrinae) and Pseudodactylogyrus (Pseudodactylogyrinae) along with Ancyrocephalus mogurndae, and marine dactylogyrids with cosmopolitan distribution, parasites of scorpaeniforms and perciforms, along with the freshwater Cichlidogyrus and Scutogyrus (infecting African cichlids [Cichlidae]) and (iii) clade C containing exclusively dactylogyrids of siluriforms, freshwater and marine, with Palaearctic, Ethiopian, Oriental and Neotropical distributions; species of Aphanoblastella and Dactylogyridae gen. sp. 4 from the Neotropical region clustering together with species allocated in the Ancylodiscoidinae, along with species of Cosmetocleithrum, Demidospermus and Dactylogyridae gen. spp. CONCLUSIONS: The position of the Ancylodiscoidinae within a larger clade of dactylogyrids (ancyrocephalines) indicates that this subfamily does not represent a natural group. Instead, species allocated to this clade (dactylogyrids of siluriforms along with species of the Ancylodiscoidinae) should be considered as a separate subfamily within the Dactylogyridae. The erection of this taxon requires the search for morphological diagnostic characters in addition to phylogenetic information. A similar strategy should be considered for a new classification of the paraphyletic Ancyrocephalinae. Members of the three clades do not seem to share obvious morphological synapomorphies nor clear patterns in host-parasite associations, zoogeographical distribution or ecology. Clade A should be considered as the Ancyrocephalinae sensu stricto since it includes the type species Ancyrocephalus paradoxus Creplin, 1839. A new subfamily should be proposed to accommodate species currently allocated to Ancyrocephalinae clustering within clade B. Future attempts to propose a new classification of the subfamilies in the Dactylogyridae should include the phylogenetically diverse Neotropical dactylogyrids.
Keywords: molekulární evoluce; sekvenční seřazení; nemoci ryb; sekvence nukleotidů; DNA helmintů; sumci; Phylogeny; Fish Diseases; Evolution, Molecular; Trematoda; Catfishes; Trematode Infections; infekce červy třídy Trematoda; DNA, Helminth; zvířata; Base Sequence; fylogeneze; Animals; Sequence Alignment